How I Became Addicted to Simulations and Games. (February 2014) - Powers, Richard B.
Three outstanding teachers stimulated my interest in alternative methods of education and made me receptive to simulations and games. At my first gaming conference, I discovered the value of simulations and games by playing games rather than by listening to lectures. I found the spirit of play and cooperation at NASAGA and ISAGA conferences refreshing and my games owe a considerable debt to the experienced gamers I met there. My experience facilitating games has taught me that allowing a few players to judge the work of their peers using subjective criteria leads to negative emotions, which may cancel any potential benefits of a game. I have also learned that the NEW COMMONS GAME, which illustrates the tragedy of the commons, may leave players feeling helpless and fatalistic about solving real-world commons problems. Several strategies are presented that counter negative feelings and instill optimism in players that commons problems can be solved. Recent developments in the video gaming community provide grounds for optimism about the future of educational gaming. However, it is imperative that video game designers who have an educational goal incorporate the knowledge that educational gamers have acquired over the past 50 years, such as the need for debriefing. A hypothetical, long-term, large-scale game is described that has the potential to educate students campuswide about how a commons resource can be sustained for the benefit of all. In addition, if the game is conducted across semesters or years, players' responsibility to future generations of players could be studied and enhanced. However, the hypothetical game would require revising current thinking about debriefing. A brief description of the games I have designed is included.